Importance of the Ports of the Province of Santa Fe in Argentina’s Agro-export Policy - Hernan Savino; Margarita Portapila; Martin Romagnoli; Melisa Orta; Adrian Bussolini (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
Argentina’s agricultural exports leave 70% of the country through the 21 ports of the province of Santa Fe. This movement is of great importance worldwide and especially in the current international conditions. From the information on the flow of ships between 2012 and 2019 available from the National Ministry of Agriculture, conclusions were drawn on the products (Soybean and Sunflower Oil, Soybean and Sunflower Pellet Corn, Wheat, Sorghum, Oats), ports and destinations. These conclusions were mapped using a vector Geographic Information System. Studies were conducted on the differences of two periods (2012-2015 / 2016-2019) very different in terms of international prices and sector regulations. Likewise, these periods correspond to national governments marked by opposing development projects. You can see the importance of each port, the added value supplied by each product according to the tons and the international quotation. The maps allow us to differentiate the areas of the world with the highest demand for each product. A fluid trade with almost all countries is observed, contrary to the widespread belief that Argentina trades with a reduced number of countries.